2003
DOI: 10.1124/dmd.31.6.694
|View full text |Cite
|
Sign up to set email alerts
|

NMR IDENTIFICATION OF AN S-LINKED GLUCURONIDE OF A TRIAZOLE THIONE FORMED IN VITRO

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:The metabolism of 3-{[3-(2-Chlorophenyl)-4,5-dihydro-5-thioxo-1H-1,2,4-triazol-1-yl]methyl}benzonitrile (AR-C133611XX) was studied in isolated dog hepatocytes. The major metabolite of AR-C133611XX was characterized by high performance liquid chromatography-mass spectrometry and NMR and found to be the product of direct glucuronidation. Evidence from 1 H and 13 C-NMR chemical shifts and a long-range proton carbon correlation experiment wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…These data confirm that the benzoxazine-2-thione (N(CϭS)O) of tanaproget did not rearrange to a thionocarbamate (N(CϭO)S) group before glucuronidation. Key 1 H and 13 C NMR chemical shift data reported above for the S-glucuronide 3 were similar to those reported in the literature for two other S-␤-(D)-glucuronides (Ethell et al, 2003;Martin et al, 2003).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…These data confirm that the benzoxazine-2-thione (N(CϭS)O) of tanaproget did not rearrange to a thionocarbamate (N(CϭO)S) group before glucuronidation. Key 1 H and 13 C NMR chemical shift data reported above for the S-glucuronide 3 were similar to those reported in the literature for two other S-␤-(D)-glucuronides (Ethell et al, 2003;Martin et al, 2003).…”
Section: Resultssupporting
confidence: 72%
“…The synthetic glucuronide 3 that was determined to be S-glucuronide was found to have retention times identical to that of metabolite M1 under all 10 HPLC conditions. Literature reports of glucuronide conjugation through an S-linkage are rare (Jeffcoat et al, 1980;Nakaoka et al, 1989;Smith et al, 1992;Ethell et al, 2003;Martin et al, 2003), with little data available on their structural characterization or the UDP-glucuronosyltransferases (UGTs) catalyzing their formation. N-and O-glucuronides are more commonly observed (Green and Tephly, 1998;Hawes, 1998;Kuehl and Murphy, 2003;Tricker, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The two-dimensional NMR experiments clearly demonstrated that the glucuronic acid linkage to BMS-204352 is through the amide nitrogen. Recently, two tautomeric S-glucuronides formed from thio-amides were reported (Ethell et al, 2003;Martin et al, 2003). Smith and Williams (1949) identified the first N-glucuronide of aniline in urine of rabbit dosed with aniline.…”
Section: Discussionmentioning
confidence: 99%
“…AR-C133611XX, a CXCR2 receptor antagonist, has been shown to be metabolized to an S-linked conjugate in dog hepatocytes as a major metabolic pathway. Structure elucidation by NMR revealed the Sglucuronide to be present on triazole thione moiety in the molecule (Martin et al, 2003). Finally, phenotyping information on formation of S-glucuronides is scarce.…”
Section: Sulfur-linked Glucuronidesmentioning
confidence: 99%